Sistema Generativo Evolutivo Multiobjetivo Para Proteções Solares Horizontais em Edificações - Lobo, Tiago Del Puppo Favilla (2024)
In hot climates, horizontal shading elements such as eaves and balconies can help reduce thermal load in indoor environments and result in lower energy consumption by cooling systems. However, depending on their size, they may also lead to reduced availability of natural light indoors. Lighting plays a lesser role in the energy efficiency of residential buildings but holds psychophysiological importance for human health. Thus, this research aimed to develop a generative system to determine the size of horizontal shading devices, achieving satisfactory thermal comfort results while ensuring greater availability of natural light, creating elements of various forms. Initially, a literature review was conducted on balconies and other horizontal shading devices and the environmental criteria for their sizing. Subsequently, through another literature review, the concept of genetic algorithms focusing on multi-objective analyses and generative design systems was presented, along with their types and examples of application for sizing shading devices. In a third stage, based on Design Science Research, the methodology for developing the generative system and respective environmental analyses was presented. Rhinoceros 6 software was used for 3D modeling, Grasshopper plugins for parametric modeling, Honeybee for environmental analyses, and Wallacei for multi-objective evaluation. Results of adaptive comfort were obtained through Operative Temperature heat maps, Thermal Comfort Percentage, and Heat Percentage. For the assessment of luminous performance, results of Daylight Autonomy, UDI 200-3000 lux, UDI<200 lux, UDI>3000 lux, and sDA were used. In a fourth stage, the algorithm of the generative system was presented, along with the results of environmental analyses compared to a generic building with shading elements of 0.5m and 3m. As a result, for the typical floor of the building, the generative system showed thermal comfort indices similar to those of the larger shading device and superior luminous performance compared to the latter, while reducing the constructed area of the elements by an average of 31.75%. Finally, concluding remarks were made to contribute to the development of the topic.